1999
DOI: 10.1146/annurev.nutr.19.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Low-Density Lipoprotein Receptor Family

Abstract: The low-density lipoprotein (LDL) receptor (LDL-R) family consists of cell-surface receptors that recognize extracellular ligands and internalize them for degradation by lysosomes. The LDL-R is the prototype of this family, which also contains very-low-density lipoprotein receptors (VLDL-R), apolipoprotein E receptor 2, LRP, and megalin. The family members contain four major structural modules: the cysteine-rich complement-type repeats, epidermal growth factor precursor-like repeats, a transmembrane domain, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
274
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(284 citation statements)
references
References 199 publications
7
274
1
2
Order By: Relevance
“…Early studies identified apoE as a key component of plasma cholesterol homeostatic mechanisms [1,2]. ApoE binds with high affinity to lipoprotein particles in the plasma compartment and acts as a ligand for receptor-mediated endocytosis via multiple members of the low-density lipoprotein receptor family [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies identified apoE as a key component of plasma cholesterol homeostatic mechanisms [1,2]. ApoE binds with high affinity to lipoprotein particles in the plasma compartment and acts as a ligand for receptor-mediated endocytosis via multiple members of the low-density lipoprotein receptor family [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The LDL receptor-related protein 1 (LRP-1) is a cell surface receptor that mediates internalization of a large number of proteins and lipoproteins including ApoEcontaining lipoproteins, very-low density lipoproteins, chylomicron remnants, activated a 2 macroglobulin, and the amyloid precursor protein (Gliemann et al, 1994;Hussain et al, 1999). LRP-1 is composed of an a chain that contains 3924 amino acids and a b chain that contains 601 amino acids (Herz et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The LDLR is known to play an important role in cholesterol homeostasis and lipid transport by mediating the cellular uptake of plasma LDL. 8,9 It has been firmly established that mutations and polymorphisms in the LDLR gene are associated with familial hypercholesterolemia (FH), obesity and atherosclerosis. [10][11][12] FH is an autosomal dominant inherited condition charac-terized by raised levels of LDL-cholesterol leading to increased risk of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%